Simultaneous cancer control and diagnosis with magnetic nanohybrid materials - Saadat, Reza; Renz, Franz (Beilstein Journal of Nanotechnology, 2016)
Coated magnetite nanoparticles were linked to 68Ga complexes used in the positron emission tomography (PET) for a new technical approach to detect cancer tissue with radiopharmaceuticals. By substitution of the Ga isotope with an alpha emitter the same compound could be used for cancer treatment. Furthermore the nanoparticles were connected to pH-sensitive complexes, enabling a pH-controlled assembly/disassembly and therefore the spreading of the particles in the tissue. With this novel method of combining detection and treatment simultaneously, the amount of medical exposure could be minimized for the patient. The results demonstrate that magnetite nanoparticles can effectively be functionalized with PET isotopes and pH sensitive complexes in order to use them as a new type of radiopharmaceuticals.
Keywords: biocompatible nanoparticles; cancer control; cancer diagnosis; magnetite nanoparticles; positron emission tomography